Erythrocytic Oxidative Stress and Haemato-biochemical Changes in Cattle, Affected with Bovine Tropical Theileriosis - Nayak, S. M.; Senapati, S. K.; Meher, S.; Samal, P.; Sethy, K.; Patra, R. C. (International Journal of Livestock Research, 2018)
Bovine Tropical Theileriosis (BTT) is caused by blood protozoa Theileria annulata in cattle, which causes high mortality among the animals and incurs huge economic losses to the farmers. It decreases the milk yield and impairs reproductive performances. Measurement of erythrocytic oxidative stress is a need of hour for effective treatment and management of this disease. Oxidative stress and lipid peroxidation in erythrocytes of cattle infected with the intra erythrocytic protozoa results in increased fragility and membrane lysis of erythrocytes which is the major concern of this study. A group of 10 cattle affected with bovine tropical theileriosis were taken as Group II along with another 10 animals (apparently healthy animal) as Group I. The erythrocytic oxidative stress indices along with the haemato-biochemical parameters were measured for both the groups. It was found that there was significant increase (p<0.05) of Malonaldehyde (MDA) value and significant decrease (p<0.05) in super oxide dismutase (SOD) and Catalase in Group II as compared to Group I. In haemato-biochemical parameters, there was significantly decreased (p<0.05) Hb, TEC, PCV, TLC, neutrophil, total protein, Albumin/Globulin ratio and increased AST and lymphocyte count was found in Group II than Group I. So it is concluded that Bovine Tropical Theileriosis (BTT) produces significant oxidative stress along with amemia and alterations in other haematobiochemical parameters.